The Impact of Tax Socialization and the Stringency of Tax Sanctions on Taxpayer Compliance Among Business Owners in the Lembang Area - Oktaviani Silaen; Hisar Pangaribuan (Yayasan Ilomata, 2023)
This research was conducted to determine the effect of tax socialization and the strictness of tax sanctions on compliance by taxpayers who own a business. The population in this study are taxpayers who have businesses in the Lembang area. The quantitative method was used in this study, with primary data obtained from the questionnaire results. Selection of the sample in this study using the method of Purposive Sampling, with a total sample of 50. Descriptive statistical tests were carried out using the SPSS version 29 program. The results showed that tax socialization did not significantly affect the compliance of taxpayers who own businesses in the Lembang area, with a test number of 0.432 < 2.01174. In contrast, the strictness of tax sanctions significantly affected the compliance of taxpayers who have businesses in the Lembang area with a test number of 0.000 < 2.01174. This study shows that the socialization of taxation and the strictness of tax sanctions significantly affect the compliance of taxpayers who have businesses in the Lembang area with a significance level of 0.000 <0.05.